an Analysis of Flipped Classroom Model Application in Learning English at Eighth Grade of SMP Negeri 4 Gunungsitoli in 2022/2023 - Lestarini Putri Zebua; Nursayani Maru’ao; Trisman Harefa; Kristof Martin Efori Telaumbanua (Journal of Education and Teaching Learning, 2023)
The purpose of research to determine and analyze the application of the flipped classroom model in English learning conducted in class VIII-F SMP Negeri 4 Gunungsitoli in 2022/2023. This researcher uses a qualitative descriptive research approach. The focus of research are first how the application of flipped classroom model in the learning English and second is what the results of students' learning English in the application of the flipped classroom model to learning English. Data sources in this study are observation, documentation, and interview.  Based on the findings of the study, it can be seen that the application of the flipped classroom model in learning English and the results of students’ learning English satisfactory, this is based on the results of observation and interview made by researcher on English teacher in class VIII-F who apply the flipped classroom model has been done well and supported from the results of interviews and from student test results that have been given by English teacher.